Thioxanthone based 9[2-(methyl-phenyl-amino)-acetyl]-thia-naphthacene-12-one as a visible photoinitiator - Dogruyol, Sevnur Keskin; Dogruyol, Zekeriya; Arsu, Nergis (ELSEVIER SCIENCE BV, 2013)
Photoinitiators that operate in the visible range of the electromagnetic spectrum have widespread applications. Thioxanthone based 9[2-(methyl-phenyl-amino)-acetyl]-thia-naphthacene-12-one (TX-MPA) was synthesized and the characterization of this initiator was confirmed by spectral analysis methods. TX-MPA has excellent absorption properties in the visible range (epsilon(480) (nm) =3576 L/mol.cm). Photophysical studies; fluorescence quantum yield (Phi(f)=0.22, DPA), phosphorescence lifetime (tau(p)=115 ms) and triplet lifetime (tau=190 ns) were explored. To explore the initiation mechanism of TX-MPA, besides the photophysical and photochemical studies, the polymer (PMMA) obtained from the photopolymerization studies was subjected to a phosphorescence study and tau(p) was found to be 105 ms compared to 115 ms for the initiator TX-MPA which proved attachment of the initiator to the polymer. Possibly both intermolecular and intramolecular hydrogen abstraction, occur during the initiation stage depending on the concentration of the initiator. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Thioxanthone based photoinitiator; Daylight polymerization; Laser flash photolysis; FREE-RADICAL POLYMERIZATION; METHYL-METHACRYLATE; EFFICIENT SYSTEMS; PHOTOPOLYMERIZATION; DERIVATIVES; COMPOSITES; CHEMISTRY; BEHAVIOR; DESIGN; Optics